Career Concerns and Resource Allocation in Conglomerates - Goel, Anand Mohan; Nanda, Vikram; Narayanan, M. P. (Review of Financial Studies, 2004)
We investigate resource allocation decisions in conglomerates when managers are motivated by career concerns. When divisional cash flows are differentially informative about managerial ability, we show that it is in the managers' interest to overallocate unobservable intangible resources to the more informative divisions. Anticipating this bias, it is optimal for the firm's owners to also overallocate observable capital to the more informative divisions. The model provides rationale for corporate socialism and corporate hedging. It also highlights a cost of segment reporting and tracking stocks, namely, that they allow managers to distort their perceived ability at the expense of investors. Copyright 2004, Oxford University Press.